2007
DOI: 10.1002/pssb.200642400
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and magnetic properties of Fe3C with 3d and 4d impurities

Abstract: We study the electronic structure, formation energies, and magnetic properties of cementite Fe 3 C doped by 3d and 4d transition metals (TM) by means of first-principles calculations. All TM elements demonstrate a preference for the substitution of the general iron position in Fe 3 C. We predict that early elements (Sc, Ti, V, Cr, Zr, and Nb) stabilize the cementite, while the end elements (Ni, Cu, Pd, and Ag) in the TM series sharply destabilize it. The magnetic properties of impurity atoms are found to depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 38 publications
6
15
1
Order By: Relevance
“…The calculations were performed for the Fe12C4 cell (four formula units), where the impurity (B, N, O, Al, Si, P, or S) occupies Fe g , Fe s , or C positions. For Fe 3 C, we obtained the optimized lattice parameters and internal atomic positions to be in good agreement with the experimental data 20–22 and other theoretical estimations 9–13, 15, 23.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The calculations were performed for the Fe12C4 cell (four formula units), where the impurity (B, N, O, Al, Si, P, or S) occupies Fe g , Fe s , or C positions. For Fe 3 C, we obtained the optimized lattice parameters and internal atomic positions to be in good agreement with the experimental data 20–22 and other theoretical estimations 9–13, 15, 23.…”
Section: Resultssupporting
confidence: 81%
“…8, where the effect of 3d impurities (Ti, V, Cr, Mn, Co, and Ni) on the chemical bonding was studied within the cluster spin‐restricted approach. Ab initio calculations gave information on the electronic structure and stability of undoped Fe 3 C 9–12 and Fe 3 C alloyed with 3d and 4d transition metals 13–16. The magnetic properties of impurities were found to depend on their atomic numbers and the trends to ferromagnetic or antiferromagnetic coupling of impurities in Fe 3 C coincide with their magnetic behavior in Fe due to the similarity of their electronic structures.…”
Section: Introductionmentioning
confidence: 99%
“…The stabilization of a carbide by an alloying element is usually given [20,27] by the change in formation enthalpy of the alloying-element-substituted carbide with respect to the pure carbide as…”
Section: Methodsmentioning
confidence: 99%
“…In Fe 3 C; when substitution of the alloying elements is considered only on the metal site, all alloying elements prefer to occupy the 8d site. [20,31] When P and S are substituted on the metal sites, it is observed that there is a major reorganization of the nearest neighbor atoms. Fe atoms are observed to move closer to the P and S atoms, both of which have p valence electrons.…”
Section: Site Preference Of Alloying Elements In the Carbidesmentioning
confidence: 99%
See 1 more Smart Citation